Knowledge Services. A Strategic Framework for the 21st Century Organization - St. Clair, Guy (Current Topics in Library and Information Practice, 2017)
Knowledge services converges information management, knowledge management (KM), and strategic learning into a single enterprise-wide discipline for the benefit of the business or organization in which it is practiced. With the success of knowledge services as a management methodology, the practice has become an acknowledged framework for strategic knowledge management applicable to all businesses and organizations.